Analysis and Derivation of Optimum Data-Driven Approach for Detecting DDoS Attacks - et al., R. Sathya (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
DDoS (Distributed Denial of Service) attacks at the application layer are exceedingly difficult to detect and minimise. HTTP flooding, XML attacks, DNS attacks, and other application-layer attacks are all possible. HTTP flooding is the most well-known and well-known application-layer attack. In PC organisations, HTTP flooding detection and relief is a fascinating research subject. Various approaches based on distributed networks with some problems counting packets or redundant submissions sent from a malicious device are used to protect against these attacks. Owing to a lack of communication equipment, this is the case. Two limitations are used to mitigate all packet flood and imitation flood attacks. Claim-carry-and-check can quickly detect violations of both limits. The search for inconsistency against full statements is easy. This was created with a distributed system in mind. Furthermore, it allows for a small number of attackers to collide. A new vulnerability known as Ad Hoc Flooding Attack triggers a denial of service when used by all on-request ad hoc networks routing protocols. To preoccupy bandwidth and clog up the link, the malicious user either transmits a substantial percentage of route request packets for devices that are not present in networks or delivers a large number of data packets.